An Ethnographic Lenses on Mathematical Activities in Kewrat Culture - Das, Akhilesh Kumar; Gautam, Dandapani (Academic Journal of Sukuna, 2025)
A study explores the mathematical knowledge embedded in the daily practices of the Kewrat community of Nepal. Employing an ethnography research design, with aims to identify the traditional counting, measurement, and geometrical concepts used by the Kewrat people and their potential pedagogical applications. The information from respondents selected with purpose sampling of 5 - elderly community members, 2 - native school teachers, 10 – students from Kewrat family and their parents with interview, observation and photographs, shows that that mathematical practices in the Kewrat culture is based on counting, measuring, arithmetic operations and geometrical principles. The study found that “ganda," "vira," "vanja," and "skori” are used in counting, fingers and hands are used for arithmetic operations, indigenous measurement tools are "dandi" for weight, “lota" and "kat-tha" for volume, and "bitta" and "haat" for measuring length and calculating area. Kewrat people also demonstrate a practical understanding of geometrical concepts, such as cones, cylinders, and prisms, applied in crafting tools for daily uses. These findings highlight the richness of cultural mathematics and its relevance to formal education. This study suggests incorporating these traditional practices into mathematics classrooms to enhance student engagement, promote hands-on learning, and connect cultural knowledge with academic concepts.